Long-Term Financing Challenges for Companies in Maintaining Business Expansion and Innovation - Ramadhan, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study investigates long-term financing companies' challenges in sustaining business expansion and innovation. It aims to identify the barriers to accessing sustainable funding, analyze their implications for innovation, and propose strategies to address these constraints across various sectors. Research Design and Methodology: The research employs a Systematic Literature Review (SLR) to analyze existing studies and synthesize findings from diverse industries, including technology, manufacturing, and clean energy. Theoretical frameworks such as Agency Theory and the Resource-Based View (RBV) guide the interpretation of findings, focusing on regulatory and market dynamics, corporate strategies, and innovation processes. Findings and Discussion: The study reveals key barriers, including regulatory rigidity, market volatility, and limited access to capital markets, which create significant imbalances between corporate financing needs and market preferences. These constraints hinder companies from pursuing long-term investments, particularly in R&D and technology development, affecting their capacity for sustained innovation. Strategies such as funding diversification, financial risk management, and cross-sector collaborations emerge as effective solutions. The interplay between regulatory frameworks and market mechanisms is highlighted as a challenge and an opportunity to enhance financing accessibility. Implications: The findings offer valuable insights for policymakers, financial institutions, and corporate managers. Policymakers are encouraged to design regulatory frameworks and incentives that align with market needs, while businesses are advised to adopt innovative financial strategies and foster collaborative ecosystems. The study contributes to the theoretical discourse on financing and innovation and provides practical recommendations for promoting sustainable business growth.